The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1982
DOI: 10.1113/jphysiol.1982.sp014282
|View full text |Cite
|
Sign up to set email alerts
|

Control of evaporative heat loss during changes in plasma osmolality in the cat

Abstract: SUMMARY1. The effects of intravenous infusion of hypertonic saline and distilled water into normally hydrated and dehydrated cats have been examined at both high and neutral ambient temperatures.2. In hydrated cats measurements of body temperature (Tb) and evaporative heat loss (e.h.l.) show that infusion of 30 % saline (1I5 ml./kg) at an ambient temperature of 38 0C, lowers e.h.l. by an average of 0-21 W/kg (P < 0-001) and elevates Tb by 0 43 'C (P < 0-01). 3. At 25 'C alterations in these two parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…The subsequent elucidation of a hormonal mechanism underlying cold diuresis (6), and the discovery of VP as an antidiuretic agent linked the phenomenon of cold diuresis to inhibition of VP secretion. The more recent observations that dehydration reduces evaporative cooling responses resulting in hyperthermia (7,57) further supports the importance of mechanisms integrating thermal and fluid homeostasis.…”
Section: Integration Of Temperature and Fluid Homeostasismentioning
confidence: 92%
“…The subsequent elucidation of a hormonal mechanism underlying cold diuresis (6), and the discovery of VP as an antidiuretic agent linked the phenomenon of cold diuresis to inhibition of VP secretion. The more recent observations that dehydration reduces evaporative cooling responses resulting in hyperthermia (7,57) further supports the importance of mechanisms integrating thermal and fluid homeostasis.…”
Section: Integration Of Temperature and Fluid Homeostasismentioning
confidence: 92%
“…In the only study of the activity of these venous structures in intact animals, Johnsen et al (1987) Dehydrated mammals can save water by reducing thermoregulatory evaporation and allowing the body temperature to rise during heat stress (Schmidt-Nielsen, Schmidt-Nielsen, Jarnum & Houpt, 1957). One mechanism for this readjustment of thermoregulation has been thought to be an osmotically induced reduction in the sensitivity of the hypothalamus to increased temperature (Baker & Doris, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The PO/anterior hypothalamus contains abundant warmsensitive neurons 12) , which are involved in various autonomic and behavioral thermoregulatory processes 17,[73][74][75][76][77] . Baker and Doris 6,7) first reported that osmotic stimulation attenuated evaporative heat loss at the level of the hypothalamus. Nakashima et al 78) showed that, in an in vitro slice of rat brain, the warm-sensitive neurons in the medial PO lower the firing rate in a hyperosmotic medium.…”
Section: Non-thermoregulatory Factors Influencing On Thermoregulationmentioning
confidence: 99%
“…The two factors attenuate both evaporative and non-evaporative heat loss mechanisms, e.g. saliva spreading and tail blood flow in rats, and panting and skin blood flow in dogs [7][8][9][10][11] . These responses would be important in preserving body fluid and preventing excessive blood distribution to the periphery; however, animals may lose thermal homeostasis.…”
Section: Non-thermoregulatory Factors Influencing On Thermoregulationmentioning
confidence: 99%
See 1 more Smart Citation